2021
DOI: 10.12688/f1000research.52528.1
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterisation of alginate hydrocolloid film dressing loaded with gallic acid for potential chronic wound healing

Abstract: Background: A dramatic growth in the prevalence of chronic wounds due to diabetes has represented serious global health care and economic issues. Hence, there is an imperative need to develop an effective and affordable wound dressing for chronic wounds. Recent research has featured the potential of bioactive compound gallic acid (GA) in the context of wound recovery due to their safety and comparatively low cost. However, there is a scarcity of research that focuses on formulating GA into a stable and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Previous studies showed that plant extracts rich in gallic acid and tannins can accelerate wound repair. 30,[44][45][46] Our data showed that PE can improve wound closure in vitro and in vivo, and these results are supported by other works. 34,47 Likewise, when human keratinocytes were treated with gallic acid at 10, 20, 50, 100, or 200 μM, this compound increased wound closure and cell migration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies showed that plant extracts rich in gallic acid and tannins can accelerate wound repair. 30,[44][45][46] Our data showed that PE can improve wound closure in vitro and in vivo, and these results are supported by other works. 34,47 Likewise, when human keratinocytes were treated with gallic acid at 10, 20, 50, 100, or 200 μM, this compound increased wound closure and cell migration.…”
Section: Discussionsupporting
confidence: 90%
“…Bioactive natural products can optimize the wound healing process. Previous studies showed that plant extracts rich in gallic acid and tannins can accelerate wound repair 30,44–46 . Our data showed that PE can improve wound closure in vitro and in vivo, and these results are supported by other works 34,47 .…”
Section: Discussionsupporting
confidence: 88%
“…To decide the substance's melt point, a little quantity of the drug was put in a capillary tube that was closed at one end. It is additionally linked to the thermometer that is positioned in the middle of a heating bath in order to track the temperatures at which melting begins and stops and to gradually heat the bath [7].The equilibrium solubility method was used to calculate the solubility. Separate doses of gallicacid were injected into screw-capped beaker vials that held 5ml of the solvent [8].…”
Section: Determination Of Melting Point and Solubilitymentioning
confidence: 99%
“…Despite this, gallic acid’s low solubility and susceptibility to environmental factors have limited its application in the pharmaceutical industry. The beneficial characteristics of GA provide the potential for it to be developed into a useful agent for the treatment of wounds [ 22 ].…”
Section: Introductionmentioning
confidence: 99%